Pressure-induced unfolding of the molten globule of all-Ala alpha-lactalbumin. - Lassalle, M; Li, H; Yamada, H; Akasaka, K; Redfield, C (2003)
Pressure-induced unfolding of a molten globule (MG) was studied in a residue-specific manner with (1)H-(15)N two-dimensional NMR spectroscopy using a variant of human alpha-lactalbumin (alpha-LA), in which all eight cysteines had been replaced with alanines (all-Ala alpha-LA). The NMR spectrum underwent a series of changes from 30 to 2000 bar at 20 degrees C and from -18 degrees C to 36 degrees C at 2000 bar, showing a highly heterogeneous unfolding pattern according to the secondary structural elements of the native structure. Unfolding began in the loop part of the beta-domain, and then extended to the remainder of the beta-domain, after which the alpha-domain began to unfold. Within the alpha-domain, the pressure stability decreased in the order: D-helix approximately 3(10)-helix > C-helix approximately B-helix > A-helix. The D-helix, C-terminal 3(10)-helix and a large part of B- and C-helices did not unfold at 2000 bar, even at 36 degrees C or at -18 degrees C. The results verify that the MG state consists of a mixture of variously unfolded conformers from the mostly folded to the nearly totally unfolded that differ in stability and partial molar volume. Not only heat but also cold denaturation was observed, supporting the view that the MG state is stabilized by hydrophobic interactions.